Mechanical, thermal and physical characteristics of oil palm (Elaeis Guineensis) fiber reinforced thermoplastic composites for FDM – Type 3D printer - Ahmad, Mohd Nazri; Ishak, Mohamad Ridzwan; Mohammad Taha, Mastura; Mustapha, Faizal; Leman, Zulkiflle; Irianto, Unfound (Elservier, 2023)
Currently, many studies of fused deposition modeling (FDM) focus on the development of new composite materials. For this reason, in order to enhance the quality of the printed parts, it is crucial to study the properties of a newly developed material for FDM. This study aims to investigate the effect of fiber on the mechanical, thermal, and physical characteristics of thermoplastic composites reinforced with oil palm fiber. The samples were characterized using mechanical and physical testing, Fourier-transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and scanning electron microscopy (SEM). The results show the 3 wt fiber composite had slightly higher tensile strength and modulus than plain ABS. Unfortunately, as oil palm fiber loading increased from 0 to 7 wt, flexural strength results showed a declining trend, and the opposite happened for modulus values. Additionally, after the fiber was added, the thermal stability improved and intermolecular hydrogen bonding increased. A composite sample became more resistant to moisture when more fibers were added. 7 wt oil palm fiber composite showed better dimension stability than 3 and 5 wt, according to a thickness swelling test. As a result, oil palm fiber reinforced thermoplast